2001
DOI: 10.1097/00006231-200108000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Whole body PET for the evaluation of bony metastases in patients with breast cancer: comparison with 99Tcm-MDP bone scintigraphy

Abstract: The purpose of this study was to determine the potential role of positron emission tomography (PET) using 2-[18F]-fluoro-2-deoxy-D-glucose (FDG) for the evaluation of bony metastasis compared with 99Tcm-methylene diphosphonate (99Tcm-MDP) bone scintigraphy in patients with breast cancer. Fifty-one female patients with breast cancer who had PET together with a bone scan within 1 month between September 1994 and March 1997 were included in this study. The median age was 49 years (range 29-79 years). The sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(56 citation statements)
references
References 13 publications
3
46
0
7
Order By: Relevance
“…Previous studies have shown that PET or PET/CT may be superior to SS for the detection of bone metastases [22][23][24][25][26][27][28]. Our results indicated that PET/CT was superior to SS in the detection of bone metastases.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have shown that PET or PET/CT may be superior to SS for the detection of bone metastases [22][23][24][25][26][27][28]. Our results indicated that PET/CT was superior to SS in the detection of bone metastases.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have found that 18 F-FDG PET/CT is more efficient than bone scintigraphy in detecting lytic and mixed bone metastases and bone marrow involvement, but it sometimes lacks sensitivity to sclerotic bone metastasis, and a multimodality approach is suggested [18,23]. In our study, five metastatic bone lesions were detected by 18 F-FDG PET/CT and the bone scan.…”
Section: F-fdg Pet/ctmentioning
confidence: 48%
“…For detection of skeletal metastases and staging of cancer, 18 F-FDG PET or PET/CT has shown higher sensitivity or specificity than BS in most reported studies (58,59) and metaanalyses (14,16,60). The improvement in sensitivity over that of BS may be due to the ability to detect metastatic tumor cells in the bone marrow before there is a sufficient osteoblastic effect to allow detection by bone-specific tracers.…”
Section: F-fdg Petmentioning
confidence: 99%